O que há de justo no comércio justo?: Estudo da cooperativa Coosturart - Epelbaum, Vanessa Janni (2010)
The Fair Trade movement presents dynamics that correlate politics and markets. It is a model that can be a symbol of a distinct commerce, where both producers and consumers get good results. Being an alternative to the conventional comercial system it aims at eliminating the figure of the self regulating market, characterized for the compulsory search of marginal utility and the auto-interest, substituting it for a new market regulated by principles of solidarity. This dissertation analyzes Fair Trade under two different points of view: conceptual and practical. The political and ethical approach, which has mobilized the researchers for the fact of the double condition to act inside and against the Market Therefore Fair Trade would be an alternative for work generation and income for groups of production in commercial disadvantage and the perspective of these groups in the current context. During the month of May, June and July of 2010, visits were made to COOSTURART. Interviews were conducted with the President and the cooperatives. All interviews were recorded and subjected to discourse analysis. The Popular Cooperative COOSTURART served as a case study to (re) think and to correlate the theoretical questions with the practical one. It represents an experience of international scope that allowed them to observe as the practical one of Fair Trade in a local scale occurs, but that occurs in a context of national and global economicsocial iniquities. The field research demonstrated that not all cooperated had obtained to incorporate logic of cooperative work and, despite COOSTURART corroborates exactly with some principles conducted Fair Trade as seen in the bibliographical research and documentary, incipient as well as it is in Brazil.